Critical Role of Area Weighting on Estimated Long-Term Global Warming and Heat Wave Trends - Ju, Seon-Dae; Choi, Won-Jun; Song, Hwan-Jin (AppliedMath, 2024)
Regular longitude-latitude grids are commonly used in reanalysis and climate prediction model datasets. However, this approach can disproportionately represent high-latitude regions if simple averaging is applied, leading to overestimation of their contribution. To explore the impact of Earth’s curvature on global warming and heat wave frequency, this study analyzed 450 years of surface temperature data (1850–2300) from a climate prediction model. When area weighting was applied, the global average temperature for the 1850–2300 period was found to be 8.2 °C warmer than in the unweighted case, due to the reduced influence of colder temperatures in high latitudes. Conversely, the global warming trend for the weighted case was 0.276 °C per decade, compared to 0.330 °C per decade for the unweighted case, reflecting a moderation of the polar amplification trend. While unweighted models projected a 317% increase in the frequency of global heat waves above 35 °C by 2300 compared to 1850, the weighted models suggested this frequency might be overestimated by up to 5.4%, particularly due to reduced weighting for subtropical deserts relative to tropical regions. These findings underscore the importance of accounting for Earth’s curvature in climate models to enhance the accuracy of climate change projections.